2014
DOI: 10.1002/etc.2522
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the sensitivity of coastal Antarctic zooplankton communities to diesel fuel: A comparison between single‐ and multi‐species toxicity tests

Abstract: Despite increasing human activity and risk of fuel spills in Antarctica, little is known about the impact of fuel on Antarctic marine fauna. The authors performed both single- and multi-species (whole community) acute toxicity tests to assess the sensitivity of an Antarctic coastal zooplankton community to the water-accommodated fraction of Special Antarctic Blend diesel. Single-species tests using abundant copepods Oncaea curvata, Oithona similis, and Stephos longipes allowed comparisons of sensitivity of key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…EC10s are based on integrated, time‐weighted total hydrocarbon content exposure concentrations (µg/L), as per Brown et al and Payne et al .…”
Section: Resultsmentioning
confidence: 99%
“…EC10s are based on integrated, time‐weighted total hydrocarbon content exposure concentrations (µg/L), as per Brown et al and Payne et al .…”
Section: Resultsmentioning
confidence: 99%
“…For many species, 4 d was the minimum duration required to see a substantial effect on mortality, and was reported in the present study, because this is commonly used in tests with temperate species. A test duration of 10 d has previously been used in tests with Antarctic and subantarctic species (e.g., Payne et al ; Marcus Zamora et al ; Holan et al , , ), and provides a good compromise between the shortest duration required to consistently see a response, and the extended duration that is appropriate for cold‐climate species with slow metabolic rates. For some cold‐climate species, even longer test durations (up to 4 wk) have been used (e.g., Sfiligoj et al ; Brown et al ) and may have provided more sensitive results, but, to be in keeping with the premise of the rapid method, these durations were impractical and beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that polar (Arctic and Antarctic) marine invertebrates are generally slower to respond to contaminants including metals, polycyclic aromatic hydrocarbons (PAHs), and other contaminants, than closely related temperate species (King and Riddle, 2001;Jensen et al, 2008;Jensen and Carroll, 2010;Hjorth and Nielsen, 2011;Hansen et al, 2011Hansen et al, , 2013Payne et al, 2014;Zamora et al, 2015). As stated by Payne et al (2014, p883), based on Peck (2002) and other authors, "The delayed response time of cold-adapted species has been linked to slower uptake kinetics, slower growth and development, lower metabolic rates, and higher lipid storage of organisms at low temperatures."…”
Section: Evidence For Delayed Toxicity In Cold Watersmentioning
confidence: 97%